Hydrogen-Bonding Interactions of 8-Substituted Purine Derivatives - Osifová, Zuzana; Šála, Michal; Dračínský, Martin (ACS omega, 2023)
Hydrogen bonding between nucleobases is a crucial noncovalent interaction for life on Earth. Canonical nucleobases form base pairs according to two main geometries: Watson-Crick pairing, which enables the static functions of nucleic acids, such as the storing of genetic information; and Hoogsteen pairing, which facilitates the dynamic functions of these biomacromolecules. This precisely tuned system can be affected by oxidation or substitution of nucleobases, leading to changes in their hydrogen-bonding patterns. This paper presents an investigation into the intermolecular interactions of various 8-substituted purine derivatives with their hydrogen-bonding partners. The systems were analyzed using nuclear magnetic resonance spectroscopy and density functional theory calculations. Our results demonstrate that the stability of hydrogen-bonded complexes, or base pairs, depends primarily on the number of intermolecular H-bonds and their donor-acceptor alternation. No strong preferences for a particular geometry, either Watson-Crick or Hoogsteen, were found.